Achieving independent control of core diameter and carbon shell thickness in Pd-C core–shell nanoparticles by gas phase synthesis. (28th June 2017) - Singh, Vinod; Mehta, B R; Sengar, Saurabh K; Karakulina, Olesia M; Hadermann, Joke; Kaushal, Akshey
Abstract: Pd-C core–shell nanoparticles with independently controllable core size and shell thickness are grown by gas phase synthesis. First, the core size is selected by electrical mobility values of charged particles, and second, the shell thickness is controlled by the concentration of carbon precursor gas. The carbon shell grows by adsorption of carbon precursor gas molecules on the surface of nanoparticles, followed by sintering. The presence of a carbon shell on Pd nanoparticles is potentially important in hydrogen-related applications operating at high temperatures or in catalytic reactions in acidic/aqueous environments.